THE EXTENDED ODD FRÉCHET INVERTED EXPONENTIAL DISTRIBUTION: PROPERTIES AND APPLICATION - Adubisi, Obinna; Ikwuoche, John; Adubisi, Chidi (Journal of Statistical Modeling and Analytics (JOSMA), 2023)
This research introduces a new three-parameter continuous distribution from the extended odd Fréchet (EOF) family of distributions called the extended odd Fréchet inverted exponential (EOFIE) distribution. Derivations of EOFIE distribution statistical properties are derived and its parameters are estimated using the technique of maximum likelihood (ML) estimation. The ML estimates finite sample performance of the EOFIE distribution is evaluated through simulation. Results obtained from the application of the EOFIE distribution to two real-life datasets showed that it provides a better fit than other competing distributions.